Day trading and swing trading the currency market : technical and fundamental strategies to profit from market moves - Lien, Kathy, 1980-; Lien, Kathy, 1980- (Hoboken : Wiley, 2015)
"Play the forex markets to win with this invaluable guide to strategy and analysis Day Trading and Swing Trading the Currency Market gives forex traders the strategies and skills they need to approach this highly competitive arena on an equal footing with major institutions. Now in it's third edition, this invaluable guide provides the latest statistics, data, and analysis of recent events, giving you the most up-to-date picture of the state of the fast-moving foreign exchange markets. You'll learn how the interbank currency markets work, and how to borrow strategy from the biggest players to profit from trends. Clear and comprehensive, this book describes the technical and fundamental strategies that allow individual traders to compete with bank traders, and gives you comprehensive explanations of strategies involving intermarket relationships, interest rate differentials, option volatilities, news events, and more. The companion website gives you access to video seminars on how to be a better trader, providing another leg up in this competitive market. The multi-billion-dollar foreign exchange market is the most actively traded market in the world. With online trading platforms now offering retail traders direct access to the interbank foreign exchange market, there's never been a better time for individuals to learn the ropes of this somewhat secretive area. This book is your complete guide to forex trading, equipping you to play with the big guys and win--on your own terms. Understand how the foreign currency markets work, and the forces that move them Analyze the market to profit from short-term swings using time-tested strategies Learn a variety of technical trades for navigating overbought or oversold markets Examine the unique characteristics of various currency pairs Many of the world's most successful traders have made the bulk of their winnings in the currency market, and now it's your turn. Day Trading and Swing Trading the Currency Market is the must-have guide for all foreign exchange traders"--
Machine generated contents note: Preface About the Author Chapter 1: Foreign Exchange -- The Fastest Growing Market of Our Time EURUSD and Corporate Profitability Nikkei and US dollar George Soros Chinese Yuan Revaluation and Bonds Comparing the FX Market with Futures and Equities FX versus Futures Who Are the Players in the FX Market? Chapter 2: Historical Events in the FX Markets Bretton Woods: Anointing the Dollar as the World Currency (1944) The End of Bretton Woods: Free Market Capitalism is Born (1971) Plaza Accord -- Devaluation of the US Dollar (1985) George Soros -- The Man Who Broke the Bank of England Asian Financial Crisis (1997-98) Introduction of the Euro (1999) Chapter 3: What Moves the Currency Market? Fundamental Analysis Technical Analysis Currency Forecasting -- What Bookworms and Economists Look At Chapter 4: A Deeper Look at the FX Market What Are the Best Times to Trade for Individual Currency Pairs? Chapter 5: What Are the Most Market Moving Economic Data Relative importance of data changes over time Chapter 6: What Are Currency Correlations and How To Use Them Positive/Negative Correlations -- What They Mean and How to use them Chapter 7: Trade Parameters for Various Market Conditions Keep a Trading Journal Identifying a Trading Environment Risk Management Chapter 8: Technical Trading Strategy: Multiple Time Frame Analysis Chapter 9: Technical Strategy: Trading with Double Bollinger Bands Using Double Bollinger Bands to Pick Tops and Bottoms Chapter 10: Technical Trading Strategy: Fading the Double Zeros Strategy Rules Chapter 11: Technical Trading Strategy: Waiting for the Deal Strategy Rules Chapter 12: Technical Trading Strategy: Inside Days Breakout Play Strategy Rules Chapter 13: Technical Trading Strategy: Fader Rules Chapter 14: Technical Trading Strategy: 20-day Breakout Trade Strategy Rules Chapter 15: Technical Trading Strategy: Channels Examples Chapter 16: Technical Trading Strategy: Perfect Order Examples Chapter 17: Fundamental Trading Strategy: Pairing Strong with Weak Chapter 18: Fundamental Trading Strategy: The Leveraged Carry Trade How Do Carry Trades Work? Why Do Carry Trades Work? When Will Carry Trades Work Best? How much risk are you willing to take? When Will Carry Trades not Work The Importance of Risk Aversion Chapter 19: Fundamental Trading Strategy: Macro Event Driven Trade Know When Big Events Occur -- Here is a List Of a Few Important Ones.... Chapter 20: Quantitative Easing and its Impact on Forex US Quantitative Easing UK Quantitative Easing Japan Quantitative Easing Eurozone Quantitative Easing Chapter 21: Fundamental Trading Strategy: Commodity Prices as a Leading Indicator The Relationship Chapter 22: Fundamental Strategy: Using Bond Spreads As a Leading Indicator for FX Calculating Interest Rate Differentials and Following the Currency Pair Trends Interest Rate Differentials: Leading Indicator, Coincident Indicator, or Lagging Indicator? Chapter 23: Fundamental Trading Strategy: Risk Reversals What Does a Risk Reversal Table Look Like? How Can You Use This Information? Chapter 24: Fundamental Trading Strategy: Using Option Volatilities To Time Market Movements How to Use Option Volatilities to Trade Forex Tracking Volatilities on Your Own: Chapter 25: Fundamental Trading Strategy: Intervention Japan Switzerland Eurozone Chapter 26: Currency Profiles and Outlook United States -- US Dollar Chapter 27: Currency Profile: Euro (EUR) Broad Economic Overview Monetary & Fiscal Policy Makers -- The European Central Bank Important Indicators for the Euro Chapter 28: Currency Profile: British Pound (GBP) Broad Economic Overview Monetary & Fiscal Policy Makers -- Bank of England Important Economic Indicators for the UK Chapter 29: Currency Profile: Swiss Franc (CHF) Broad Economic Overview Monetary & Fiscal Policy Makers -- Swiss National Bank Important Characteristics of the Swiss Franc Important Economic Indicators for Switzerland Chapter 30: Currency Profile: Japanese Yen (JPY) Economic Overview Abenomics Monetary and Fiscal Policy Makers Important Economic Indicators For Japan Chapter 31: Currency Profile: Australian Dollar (AUD) Broad Economic Overview Monetary & Fiscal Policy Important Economic Indicators for Australia Chapter 32: Currency Profile: New Zealand Dollar (NZD) Broad Economic Overview Monetary & Fiscal Policy Makers -- Reserve Bank of New Zealand Important Characteristics of the New Zealand dollar Important Economic Indicators for New Zealand Chapter 33: Currency Profile: Canadian Dollar (CAD) Broad Economic Performance Monetary & Fiscal Policy Important Economic Indicators for Canada Index .
Revised edition of the author's Day trading and swing trading the currency market, 2009.
Includes index.
Description based on print version record and CIP data provided by publisher.
Keywords: Foreign exchange futures; Foreign exchange market; Speculation; BUSINESS & ECONOMICS / Investments & Securities; Foreign exchange futures; Foreign exchange market; Speculation; Electronic books